Warriors do not abandon the battlefield: beer advertising in the 2010 Soccer World Cup - Pereira, Camila Augusta Alves (Organicom, 2011)
During the 2010 Fifa Soccer World Cup, the Brahma Chopp beer brand, official sponsor of the Brazilian soccer team, launched a television advertising campaign positioning the image of some of its players as warriors and national heroes. The study aims to analyze how the brand holds the discourse of the hero’s journey in soccer to create a sphere of identification linking the beverage brand and sports, heroes and consumers, within the context of the mythological “Brazil, the soccer country”.